Analysis of Job Satisfaction and Work Engagement Impact on Productivity Mediated by Employee Performance : Empiric Study on Profit Organization - Hedi Saepudin, Tubagus; Sjarifudin, Didin; Sinlae , Fried (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The purpose of this paper is to increase understanding of the elements that influence employee performance and provide practical guidelines for organizations in an effort to improve the productivity and job satisfaction of their employees. This paper uses quantitative research methods with analysis techniques using SPSS 25, where the object of research in a profit organization in East Jakarta with a sample of 42 random sampling. The analysis test uses T test, F test, Pearson correlation. Based on the results that have been displayed, it can be seen that Job Satisfaction (X1) has a significant effect on Productivity (Y), Work Engagement (X2) is not affected by Productivity (Y), and the variable Employee Engagement (X3) has no effect on Productivity (Y). While simultaneously from the calculation results, Job Satisfaction (X1), Work Engagement (X2), Employee Performance (Z), simultaneously affect Productivity (Y), while the rest is influenced by other factors not examined. The results of this study make a real contribution to the object and also for other researchers who will continue or research in the future.